Shopping to Get the Most for your Money - Mary N. Harrison (EDIS, 2005)
People must make choices about food, clothing, and housing as well as non-essentials. Our wants are endless, but our resources are not! To become a competent consumer, you must develop skills to serve you in a complex marketplace. When buying goods and services, if you spend your money wisely you will receive satisfaction and value for the dollars you spend. To become a competent consumer, learn to shop effectively. This document is Fact Sheet FCS 5008, a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Revised: June 2005. First published: June 1982.